Impact of EBV essential nuclear protein EBNA-3C on B-cell proliferation and apoptosis - Saha, Abhik (Future Microbiol, 2013)
For over 40 years, EBV infection has been implicated in the etiology of a variety of lymphoid malignancies with the exceptional ability to drive resting B cells to continuously proliferate by successfully overriding cellular apoptotic stimuli. EBV utilizes the normal physiology of B-cell differentiation to persist within the memory B-cell pool of the immunocompetent host and subsequently establishes a lifelong latent infection. During latency, out of a subset of viral genes expressed, EBNA-3C is one of the essential antigens required for in vitro primary B-cell transformation. EBNA-3C acts as a transcriptional coregulator by interacting with various cellular and viral factors. For the last 10 years, we have been actively engaged in discerning the biological significance of these interactions and revealed that EBNA-3C primarily targets two important cellular pathways – cell cycle and apoptosis. This review aims to summarize our current knowledge on EBNA-3C-mediated functions and describe how EBNA-3C seizes these cellular pathways that eventually promote B-cell lymphomagenesis. A scrupulous understanding of the critical relationship between EBNA-3C and these cellular machineries will not only aid in elucidating EBV pathogenesis, but also largely facilitate the development of novel diagnostic, as well as therapeutic, strategies against a vast range of EBV-associated B-cell lymphomas.